2014
DOI: 10.1016/j.stem.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Maintains Mesenchymal Stem Cell Function and Bone Homeostasis via Regulation of Ca2+ Channel Sulfhydration

Abstract: SUMMARY Gaseous signaling molecules such as hydrogen sulfide (H2S) are produced endogenously and mediate effects through diverse mechanisms. H2S is one such gasotrasmitter which regulates multiple signaling pathways in mammalian cells, and abnormal H2S metabolism has been linked to defects in bone homeostasis. Here, we demonstrate that bone marrow mesenchymal stem cells (BMMSCs) produce H2S to regulate their self-renewal and osteogenic differentiation, and H2S deficiency results in defects in BMMSC differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
246
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 231 publications
(264 citation statements)
references
References 50 publications
14
246
1
3
Order By: Relevance
“…H2S is a metabolic production of homocysteine by transsulfuration dependent on CBS, CSE, or MPST combined with cysteine aminotransferase (37). Recent studies highlight that H2S plays an essential role in osteoclast differentiation (11,23) and bone marrow MSC osteogenesis (26). In this study, we identified that osteoblasts predominantly expressed the CSE-H2S system, which sulfhydrated RUNX2 at C122 and C132 sites to increase RUNX2 activity, thereby enhancing osteoblast biologic function to promote bone fracture healing.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…H2S is a metabolic production of homocysteine by transsulfuration dependent on CBS, CSE, or MPST combined with cysteine aminotransferase (37). Recent studies highlight that H2S plays an essential role in osteoclast differentiation (11,23) and bone marrow MSC osteogenesis (26). In this study, we identified that osteoblasts predominantly expressed the CSE-H2S system, which sulfhydrated RUNX2 at C122 and C132 sites to increase RUNX2 activity, thereby enhancing osteoblast biologic function to promote bone fracture healing.…”
Section: Discussionmentioning
confidence: 76%
“…The sulfhydration modification depends on H2S generation (27). CSE or CBS knockdown had similar effects on H2S generation and osteogenesis marker expression in MSCs (26). MSCs differentiated into osteoprogenitors and then preosteoblasts (6).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations